3518 Bowel Ischemia after Continuous Flow Ventricular Assist Device Therapy: A Single Center Analysis. (27th March 2019) - Choi, Ashley Y; Anand, Jatin; Bishawi, Muath; Daneshmand, Mani A.; Schroder, Jacob N.; Agarwal, Suresh M.; Milano, Carmelo A.
Abstract : OBJECTIVES/SPECIFIC AIMS: The purpose of the study was to describe patient characteristics associated with subsequent development of bowel ischemia. Primary outcomes were survival to discharge, 30-day and 1-year survival in patients with LVAD who subsequently develop bowel ischemia. Secondary outcomes included characteristics of patients who survive to discharge after bowel ischemia and those who do not. These included markers of patient condition prior to surgical/endoscopic intervention such as lactate levels, ICU admission, ventilator dependence, vasopressor and renal replacement requirements, as well as presence of sepsis. Of these, we predicted that lactate levels and white blood cell count would be significantly elevated pre- and post-operatively in patients who do not recover from bowel ischemic event. We used Mann-Whitney U Test to examine lactate levels between the two groups as our sample size was <30 and therefore necessitated the use of non-parametric testing. METHODS/STUDY POPULATION: In this single-center retrospective study, we analyzed all patients who underwent durable, CF-LVAD implantation at Duke University Medical Center (DUMC) between January 2008 and November 2018. Patients were screened using CPT codes for abdominal surgical exploration or ICD codes for intestinal vascular insufficiency. Final cohort was selected with confirmed diagnosis of intestinal ischemia based on surgical exploration or endoscopic intervention. Patient characteristics including pre-LVAD comorbidities, indication for LVAD implant, and clinical picture prior to bowel ischemic event were collected. Specific characteristics related to bowel ischemia were summarized, including diagnostic imaging, time from imaging study to operative intervention, and intraoperative details. Patient outcomes including survival to discharge, 30-day-, and 1-year survival were summarized. Patients were stratified based on survival to discharge status. Continuous variables were reported as median and interquartile range and compared using Mann-Whitney U test. Categorical variables were reported as proportions and compared using Fisher's exact test as appropriate. RESULTS/ANTICIPATED RESULTS: A total of 754 patients underwent durable, CF-LVAD implant at DUMC, of which 21 subsequently developed intestinal ischemia (incidence 2.8%). The majority were male (81%) and treated as destination therapy (76.2%). Ten patients (50%) survived to discharge (one remains hospitalized). The proportions of patients receiving HeartMate II (60% vs. 50%, p=1.0), HeartMate III (20% vs. 10%, p=1.0), and HeartWare (20% vs. 40%, p=0.6) were not significantly different between patients who survived to discharge and patients who did not. Median time from LVAD implant to diagnosis of bowel ischemia did not vary significantly between the patient groups (11.5 days, IQR 34.75 vs. 16.5 days, IQR 173.8; p=0.40), nor did the median time from diagnosis to surgical intervention (264.5 minutes, IQR 497.8 vs. 323 minutes, IQR 440, p=0.82). In the 48 hours leading to diagnosis and intervention, renal replacement therapy (50% vs. 0%, p=0.033) was more prevalent in patients who did not survive to discharge. Differences in pre- and post-operative lactate levels were not significantly different in patient groups. A similar pattern of diagnostic study preference emerged from both groups, with CT being the most common (76.2%) followed by KUB (42.9%). Upper endoscopy/colonoscopy was performed in 7 patients (33.3%), of which 5 also had operative exploration. A total of 19 patients underwent abdominal exploration (90.5%). Nine had large bowel resection (42.9%) while 14 had small bowel resection (66.7% with average 75cm removed). Overall survival at 1-year was 33%. For those making it to discharge (n=10), one year survival was 60%. DISCUSSION/SIGNIFICANCE OF IMPACT: This is the first institutional study to our knowledge to describe intestinal ischemia in patients receiving CF-LVAD therapy. Intestinal ischemia in patients receiving CF-LVAD therapy is associated with high mortality and morbidity. Diagnosis of bowel ischemia should be considered in patients presenting with clinical symptoms of bowel ischemia in addition to requirement of renal replacement therapy. Imaging modalities used were dependent on the clinical situation and were not always necessary prior to intervention. Further investigation is warranted to identify predictors of this morbid complication.